Surface finish characteristics of titanium alloy in a non conventional technique - Md. Ashikur, Rahman Khan; M. M., Rahman (Elsevier Ltd, 2017)
A large number of parameters knowingly affect the performance of electrical discharge machining (EDM) which is a non-conventional process. The choice of parameters becomes intricate. In this view, this article presents the surface characteristics of the machined surface in EDM on titanium alloy, Ti-5Al-2.5Sn. Experimentation was carried out using negative polarity of copper (Cu), copper-tungsten (Cu-W) and graphite (Gr) electrode. Among the electrodes, the copper electrode produces the lowest surface roughness whilst graphite electrode gives the highest surface roughness. In respect of fine surface characteristics the copper can become as first choice electrode materials.